Toxic and essential metals determination in commercial seafood: Paracentrotus lividus by ICP-MS. Issue 6 (18th March 2016) - Salvo, Andrea; Cicero, Nicola; Vadalà, Rossella; Mottese, Antonio Francesco; Bua, Daniel; Mallamace, Domenico; Giannetto, Carlo; Dugo, Giacomo
Abstract : Toxic and essential metals content was determined by inductively coupled plasma mass spectrometry in commercial sea urchins samples from the Mediterranean Sea and Pacific Ocean. Results show that Chilean samples have the highest values of Cd, As, Ni, Cr and V; Spanish samples have the maximum Hg content while Sicilian samples have the lowest content of toxic metals. The toxic metal traces were compared with the limits of European Community (EC) No. 1881/2006 for bivalve molluscs. All samples exceed Pb and Cd limit levels; regarding Hg levels, only Sicilian and Sardinian samples have Hg content below the EC limits. The dietary intake of toxic and essential elements was evaluated for an adult. Furthermore, our study highlights a correlation between the toxic elements content and the marine environmental conditions of the places of origin even though only the generic FAO fishing area is specified. Abstract :